Get up, stand up: Alongside adolescents and young adults with cancer for their right to be forgotten. Issue 5 (October 2022) - Quarello, Paola; Toss, Angela; Mascarin, Maurizio; Banna, Giuseppe Luigi; Canesi, Marta; Milano, Giuseppe Maria; Incorvaia, Lorena; Lambertini, Matteo; Terenziani, Monica; Clerici, Carlo Alfredo; Vigevani, Giulio Enea; Beretta, Giordano Domenico; et al.
Adolescent and young adult cancer survivors may experience various forms of social difficulties years or even decades after completing their cancer treatments. This article will hopefully help the Italian national project dedicated to adolescents and young adults with cancer promoting political and legal solutions to stop discrimination and supporting the right to be forgotten.